PUNCH DESIGN INFLUENCE ON STAMPABILITY (Engineering Review, 2009)
Alterations are often necessary during the tryout of stamping tools. These changes may range from adjustments on die and punch design to the selection of a new material with better formability characteristics. The identification of regions in the workpiece where stretching, deep drawing and/or plane strain will occur during the forming process can allow the process to work smoothly through the tools’ geometry optimization. Nowadays, increasing attention has focused on a material evaluation based on tool geometries. In this work, the effect on the Forming Limit Curve of four punch models with varying geometries was analyzed in addition to the traditional Nakazima test tool. It was found that a marked reduction in the tool’s radiuses (R1 and R2 radii) reduces the material forming potential by decreasing the major true strain.